'Final solution' : Nazi population policy and the murder of the European Jews - Aly, Götz 1947- (Arnold, 1999)
Making extensive use of archives, Aly provides a detailed reconstruction of the Final Solution. He illustrated the lunacy of Nazi race policy and the variety of agencies that went into the gradual shaping of a policy of all-out genocide